Rebirth and Reinvention Transforming Philippine Organizations - Hechanova, Ma. Regina (Archīum Ateneo, 2012)
This book was especially written for leaders whose task is to ensure viability and success of our country's organizations and for those who have taken on the challenge of teaching and developing such leaders. In this book, we present the inspiring journeys of Filipino companies that have experienced rebirth and reinvented themselves despite the odds. We hope that this book will spark new ideas, provoke readers into deeper reflection, or at the very least, affirm with greater conviction that Filipino companies can become globally competitive and sustainable. Our dream is that we can harness the knowledge and insights shared by these Filipino leaders and organizations in order that we can eventually transform our country, one organization at a time.